War and Elections1. Issue 3 (30th October 2014) - Stevens, Daniel
Abstract : This paper argues that the effects of war as a performance issue in elections are different for a right‐wing than a left‐wing leader. War is consistent with the reputation of right‐wing, hawkish governments, but does not fit the reputation of left‐wing, dovish governments, and necessitates a turn away from the domestic issues the public expects left‐wing governments to prioritize. War therefore varies in its effects on perceptions of right‐wing and left‐wing leaders. War also provides more temptation for left‐wing supporters to defect to the incumbent under a right‐wing government than for right‐wing supporters to defect under a left‐wing government. The War in Iraq and elections in the United States and UK provide a unique case to test these arguments. The results confirm that Blair paid a higher political price as a left‐wing leader, because perceptions of Blair's trustworthiness became central to evaluations of him. Conversely, positive perceptions of strength became central to evaluations of Bush as a right‐wing leader. The war also had asymmetric effects on supporters of the opposition party in the UK that resulted in higher costs to Blair. These findings imply that the risks of going to war are greater for left‐wing leaders.